Iterative arylation of amino acids and aliphatic amines via δ‐C(sp3)−H activation: experimental and computational exploration - Guin, S; Dolui, P; Zhang, X; Paul, S; Singh, V; Pradhan, S; Chandrashekar, H; Anjana, S; Paton, RS; Maiti, D (Wiley, 2019)
Directed C-H functionalization has been realized as a complementary tool to the traditional approaches for a straightforward access of non-proteinogenic amino acids; albeit such a process is restricted mostly up to the γ-position. In the present work, we demonstrate the diversification [(hetero)arylation] of amino acids and analogous aliphatic amines selectively at the remote δ-position by tuning the reactivity controlled by ligands. An organopalladium δ-C(sp3)-H activated intermediate has been isolated and crystallographically characterized. Mechanistic investigations carried out experimentally in conjunction with computational studies shed light on the difference in the mechanistic picture depending on the substrate structure.